A Perspective of Epigenetic Regulation in Radiotherapy - Peng, Qin; Weng, Kegui; Li, Shitian; Xu, Richard; Wang, Yingxiao; Wu, Yongzhong (Frontiers in Cell and Developmental Biology, 2021)
Radiation therapy (RT) has been employed as a tumoricidal modality for more than 100 years and on 470,000 patients each year in the US. The ionizing radiation causes genetic changes and results in cell death. However, since the biological mechanism of radiation remains unclear, there is a pressing need to understand this mechanism to improve the killing effect on tumors and reduce the side effects on normal cells. DNA break and epigenetic remodeling can be induced by radiotherapy. Hence the modulation of histone modification enzymes may tune the radiosensitivity of cancer cells. For instance, histone deacetylase (HDAC) inhibitors sensitize irradiated cancer cells by amplifying the DNA damage signaling and inhibiting double-strand DNA break repair to influence the irradiated cells' survival. However, the combination of epigenetic drugs and radiotherapy has only been evaluated in several ongoing clinical trials for limited cancer types, partly due to a lack of knowledge on the potential mechanisms on how radiation induces epigenetic regulation and chromatin remodeling. Here, we review recent advances of radiotherapy and radiotherapy-induced epigenetic remodeling and introduce related technologies for epigenetic monitoring. Particularly, we exploit the application of fluorescence resonance energy transfer (FRET) biosensors to visualize dynamic epigenetic regulations in single living cells and tissue upon radiotherapy and drug treatment. We aim to bridge FRET biosensor, epigenetics, and radiotherapy, providing a perspective of using FRET to assess epigenetics and provide guidance for radiotherapy to improve cancer treatment. In the end, we discuss the feasibility of a combination of epigenetic drugs and radiotherapy as new approaches for cancer therapeutics.